Okay, I modeled the beginning of the question as:

x + y = 50

with x = Dad; y = Jill

In 5 years, Jill will be five years older, which can be expressed as:

y+5

At this point in time, Dad will be three times Jill's age, which is:

3(y+5)

Here is the tricky part: Both of them have aged 5 years, so when you set up the equation it looks like:

3(y+5) + (y+5) = 50 + 5 + 5

4(y+5) = 60

y+5 = 15

y=10

Substitute y back into original equation to find Dad's Age:

x + 10 = 50

x = 40

And the ages work out in 5 years because Jill will be 15 and Dad will be 45:

45 = 15*3

Hope this helps.